PENGARUH DAR DAN DER TERHADAP ROA DAN ROE PADA PERUSAHAAN MAKANAN DAN MINUMAN - Nur, Meilani; Ayunda Rahmawati, Dayyinah (Cross-border, 2023)
This research examines the relationship between the Debt to Asset Ratio (DAR) and the Debt to Equity Ratio (DER) with financial performance indicators, Return on Assets (ROA) and Return on Equity (ROE), in 28 food and beverage companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2022. Using multiple regression analysis with IBM SPSS 24, the study aims to determine whether financial leverage significantly influences profitability in this sector. The findings indicate that both DAR and DER do not have a significant impact on ROA and ROE, suggesting that other factors, such as operational efficiency, market conditions, and company-specific strategies, may play a more critical role in determining financial performance. These results provide valuable insights for industry players and policymakers regarding the limitations of financial leverage in improving profitability. Future research could expand the sample size, incorporate additional financial indicators, or explore different industry sectors to gain a more comprehensive understanding of this relationship.